Recombinant Anthrax Toxin Receptor-Fc Fusion Proteins Produced in Plants Protect Rabbits against Inhalational Anthrax - Wycoff, Keith L. (American Society for Microbiology (ASM), 2011)
Inhalational anthrax, a zoonotic disease caused by the inhalation of Bacillus anthracis spores, has a ∼50% fatality rate even when treated with antibiotics. Pathogenesis is dependent on the activity of two toxic noncovalent complexes: edema toxin (EdTx) and lethal toxin (LeTx). Protective antigen (PA), an essential component of both complexes, binds with high affinity to the major receptor mediating the lethality of anthrax toxin in vivo, capillary morphogenesis protein 2 (CMG2). Certain antibodies against PA have been shown to protect against anthrax in vivo. As an alternative to anti-PA antibodies, we produced a fusion of the extracellular domain of human CMG2 and human IgG Fc, using both transient and stable tobacco plant expression systems. Optimized expression led to the CMG2-Fc fusion protein being produced at high levels: 730 mg/kg fresh leaf weight in Nicotiana benthamiana and 65 mg/kg in N. tabacum. CMG2-Fc, purified from tobacco plants, fully protected rabbits against a lethal challenge with B. anthracis spores at a dose of 2 mg/kg body weight administered at the time of challenge. Treatment with CMG2-Fc did not interfere with the development of the animals' own immunity to anthrax, as treated animals that survived an initial challenge also survived a rechallenge 30 days later. The glycosylation of the Fc (or lack thereof) had no significant effect on the protective potency of CMG2-Fc in rabbits or on its serum half-life, which was about 5 days. Significantly, CMG2-Fc effectively neutralized, in vitro, LeTx-containing mutant forms of PA that were not neutralized by anti-PA monoclonal antibodies.